Elucidating the thermal and polymerization behaviours of benzoxazines from lignin derivatives. (5th February 2020) - Trejo-Machin, Acerina; Adjaoud, Antoine; Puchot, Laura; Dieden, Reiner; Verge, Pierre
Graphical abstract: Highlights: Depolymerized lignin is a huge feedstock of phenolic compounds for benzoxazine. Model phenolic compounds were selected to design new benzoxazine. The thermal properties were reviewed to elucidate the role of the p -substituent. The substituent drives both thermal and polymerization behaviours. High thermal stability of the monomer is found for –CHO and –COOCH3 p -substituents. Abstract: Due to their abundance, biophenols are widely targeted for the design of polybenzoxazines. Among them, ortho -methoxy substituted phenolic compounds are an attractive source of inspiration, abundantly issued from polyphenol depolymerisation. In most of the cases, they are substituted in the para -position with a group affecting the thermal properties of benzoxazine. This paper challenged to elucidate the role of the p -substituents found in lignin-occurring phenolic compounds, by studying the properties of purified monomers prepared from a solvent-free condensation of furfurylamine and model molecules: vanillin (V-fa), vanillic acid (VA-fa), guaiacol (G-fa), methyl vanillate (MV-fa) and creosol (Cr-fa). G-fa and V-fa were able to form 3D networks, the first one due to its unsubstituted para -position, and the second one due to the involvement of the –CHO group during the polymerization. Interestingly, these two substituents were providing a substantial stability to the monomers upon heating. On the contrary, Cr-fa and MV-fa, which were respectively dimerizing and oligomerizing, underwent substantially degradation during their curing.